METODE DAN EVALUASI PENDIDIKAN AKHLAK DALAM HADITS NABAWI - Yanuar Arafat; Abdullah Idi; Kms. Badaruddin (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
The whole side of human life has been guided thus regularly in Islamic law. The entire rule can clearly be read, analyzed and taken to be a way of life, both of the verses of the Qur'an and the hadiths of the Prophet. Â The content of values education in the form of moral education method contained in the Prophetic hadiths is perfect. Among these are methods of moral education; exemplary method, the method of guidance and advice, methods and question and answer dialogue, education by utilizing an event), soul generation method, and the method of providing motivation and warnings. Â Moral education in the Prophetic hadiths have managed to realize the goal of moral education in all the values contained in the curriculum, both internally and externally. Internally, the application of the concept of moral education has successfully established a strong personal figure primarily spiritual. While externally, moral education has managed to establish a private figure who bring good, especially for mankind, and all beings in general.Â Kata kunci: pendidikan akhlak, metode, evaluasi, hadits nabawi.